On the emergence of public education in land-rich economies - Galiani, Sebastian (2008)
We analyze the emergence of large-scale education systems by modeling the incentives that the economic elite could have (collectively) to accept taxation destined to finance the education of credit-constrained workers. Contrary to previous work, in our model this incentive does not arise from a complementarity between physical and human capital in manufacturing. Instead, we emphasize the demand for human-capital-intensive services by high-income groups. Our model seems capable to account for salient features of the development of Latin America in the 19th century, where, in particular, land-rich countries such as Argentina established an extensive public education system and developed a sophisticated service sector before starting significant manufacturing activities.